Efficient method to obtain Platinum–Cobalt supported on graphene oxide and electrocatalyst development. (2nd October 2020) - Marinoiu, Adriana; Raceanu, Mircea; Carcadea, Elena; Andrulevicius, Mindaugas; Tamuleviciene, Asta; Tamulevicius, Tomas; Capris, Catalin; Varlam, Mihai
Abstract: We have prepared a highly efficient and stable platinum–cobalt catalyst supported on graphene oxide by using a one-step synthesis microwave-irradiation process. The structure and composition of two different compositions (Pt:Co(2.5:1)/rGO, Pt:Co(2:1)/rGO) have been investigated by Fourier infrared spectroscopy (FT-IR), X-ray Photoelectron spectroscopy (XPS), specific surface area (BET), Raman spectroscopy. Their electrocatalytic activity was investigated and the electrochemical response from cyclic voltammetry revealed the high efficiency and stability as well as the potential application as cathode electrode. The electrocatalysts exhibited a superior durability comparing with commercial Pt/C catalyst after accelerated stress test, indicating a lower loss of electrochemical surface area in the case of prepared samples. Moreover, this study extends the applicability of this synthesis method for the preparation of other noble or transitional metal nanoparticles decorated on reduced graphene oxide. Highlights: Pt–Co/rGOs are prepared using the eco-friendly microwave-assisted process. The electrochemical activity and stability were performed using the accelerated stress test. The excellent stability of electrodes was demonstrated. Platinum loading could be reduced without a significant loss of performance and durability.